2023
DOI: 10.26668/businessreview/2023.v8i10.3779
|View full text |Cite
|
Sign up to set email alerts
|

Marketing Mix on Purchase Intention and its Impact on the Decision to Purchase Somethinc Products

Achmad Manshur Ali Suyanto,
Desshandra Garcya Dewi

Abstract: Purpose: Investigate the influence of the marketing mix on consumer purchase intentions and its impact on consumer purchasing decisions for Somethinc products in Indonesia. In addition, the study analyzes the moderating effects of age, income, and culture on purchase intentions and purchase decisions.   Theoretical framework: This research utilizes the marketing mix (Product characteristics, Affordable prices, Easy access to products, and Price promotions) concept based on prior studies in the realm of marketi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…There have been many studies examining the relationship between the marketing mix and the decision to use a product/service. The research results showed that a significant influence was found on the relationship between marketing mix and usage decisions (Dewi & Hidayat, 2023;Suyanto & Dewi, 2023;Komari et al, 2020).…”
Section: Relationship Between Variablesmentioning
confidence: 99%
“…There have been many studies examining the relationship between the marketing mix and the decision to use a product/service. The research results showed that a significant influence was found on the relationship between marketing mix and usage decisions (Dewi & Hidayat, 2023;Suyanto & Dewi, 2023;Komari et al, 2020).…”
Section: Relationship Between Variablesmentioning
confidence: 99%